Planeamiento estratégico y el cumplimiento de metas en la Municipalidad distrital de Punchana 2022 - Diaz Dacosta, Beatriz (2023)
The purpose of the study was to determine the relationship between strategic planning and the achievement of goals in the District Municipality of Punchana 2022. The type of research was applied, correlated level accompanied by a nonexperimental design. It was taken as a population and sample 43 workers of said institution. The technique of the survey composed of a series of items was used. Among the results it was evidenced that the relationship is significant between strategic planning and the achievement of goals in the municipality; which was contrasted by a correlation of 0.582 and a significance of 0.000. Along the same lines, the relationship is significant between the institutional attributes and the achievement of goals in the municipality in question, this was corroborated with the correlation coefficient of 0.558 and a significance of 0.000. In addition, the relationship is significant between the strategic formulation and the achievement of goals, since after the statistical processing, a correlation coefficient of 0.559 and a significance of 0.000 have been contrasted. Finally, the relationship is significant between the evaluation of results and compliance, since a correlation coefficient of 0.614 and a significance of 0.000 have been calculated.